Family business innovativeness: a quantitative analysis of the individual and combined effect of size, age/generation and family ownership - Skrbková, Denisa; Rydvalová, Petra (Journal of Business Economics and Management, 2023)
No large-scale quantitative studies exist on how the complex characteristics of the firm affect the innovativeness of family businesses. Our study is the first to quantitatively examine how size, age/generation and family ownership individually and in combination affect the innovativeness of family businesses, using data from 56 countries. Firstly, we found that medium and large family businesses are perceived by potential successors as more innovative than small businesses; secondly, that the trend of family business innovativeness changes over time and generations according to the U-shape line; and thirdly, that the most effective family ownership in terms of innovativeness seems to be that with exactly 50%. These results were subsequently confirmed by testing the combined effect of the above mentioned three characteristics. In contrast, small family businesses in which the second or any subsequent generation is involved and which are minority or majority family-owned are perceived as the least innovative family businesses. Our findings can help public authorities in deciding how to allocate public funds, investors in deciding how to co-finance projects, and family businesses in defining development and innovation strategies for their growth.First published online 12 January 2024